Performative state capacity and climate (in)action - Immanuel Feld; Thiemo Fetzer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Climate action requires significant public- and private sector investment to achieve meaningful reductions in carbon emissions. This paper documents that large-scale austerity, coupled with barriers to flows of data and a lack of (digital) skills in (local) government, may have been a significant barrier to delivering climate action in the form of retrofitting. Decomposing heterogeneity in estimated treatment effects of a large-scale energy efficiency savings program that was rolled out through a regression discontinuity design in the early 2010s, we find that both the extent of austerity - induced local budget cuts and poor digital connectivity - may be responsible for up to 30% fewer retrofit installations that counterfactually would have taken place had it not been for austerity.
Keywords: Q54; Q58; H76; C21; O33; R11; H54; 330; state capacity; austerity; skills; climate action; public economics